Burkitt's lymphoma mimicking EBV disease as first sign of vertical HIV infection in an adolescent - Lombardi Alessandra; De Vito Rita; Pontrelli Giuseppe; Tchidjou Hyppolite K; Aquilani Angela; Mora Nadia; Santilli Veronica; Bernardi Stefania; Palma Paolo (BMC, 2010)
Abstract Burkitt's Lymphoma (BL) rarely represents the first clinical manifestation of vertical HIV infection in adolescent in Western Europe. We report the case of a 17 year-old boy with two week history of fever and enlarged cervical lymph nodes firstly misdiagnosed as EBV infection, subsequently diagnosed as Burkitt's Lymphoma and vertical HIV infection.